2013
DOI: 10.1111/1753-0407.12093
|View full text |Cite
|
Sign up to set email alerts
|

CDKAL1 and HHEX are associated with type 2 diabetes‐related traits among Yup'ik people (在尤皮克人群中CDKAL1HHEX与2型糖尿病相关特征有关)

Abstract: Background: Genome-wide association studies (GWAS) have identified single nucleotide polymorphisms (SNPs) associated with type-2 diabetes (T2D), mainly among individuals of European ancestry. We examined the frequency of these SNPs and their association with T2D-related traits in an Alaska Native study population with a historically low prevalence of T2D. We also investigated whether dietary characteristics that may protect against T2D, such as n-3 polyunsaturated fatty acid (n-3 PUFA) intake, modify these ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Each risk allele of the 10 selected SNPs contributed to increasing the risk of T2DM by 1.111 to 1.293 folds. In a European‐American population KCNQ1 rs163177 had a positive association with T2DM risk . However, KCNQ1 rs163177 has not been reported to be associated with T2DM in Asians, including Chinese.…”
Section: Discussionmentioning
confidence: 91%
“…Each risk allele of the 10 selected SNPs contributed to increasing the risk of T2DM by 1.111 to 1.293 folds. In a European‐American population KCNQ1 rs163177 had a positive association with T2DM risk . However, KCNQ1 rs163177 has not been reported to be associated with T2DM in Asians, including Chinese.…”
Section: Discussionmentioning
confidence: 91%
“…However, as a validated biomarker of marine food (fish and marine mammal) intake for the Yup’ik population of SW Alaska, the RBC δ 15 N value has been used to examine how gene × diet interactions are associated with risk factors for obesity and chronic disease (2, 71, 81, 82), and it was recently used to demonstrate that high and low consumers of marine foods exhibit very different patterns of gene methylation (3). We found that the RBC δ 15 N value captured most of the same diet - risk factor associations that were previously identified for Yup’ik people using RBC EPA and DHA (84), but that in addition, high RBC δ 15 N values were associated with high adiponectin, which promotes insulin sensitivity, and were inversely associated with blood pressure (102).…”
Section: Stable Isotope Ratios In Human Dietary Studiesmentioning
confidence: 99%
“…Additionally, the HHEX gene rs5015480 C allele was significantly associated with increased fasting glucose and HbA 1c levels (29). Additionally, the HHEX gene rs5015480 C allele was significantly associated with increased fasting glucose and HbA 1c levels (29).…”
Section: Discussionmentioning
confidence: 98%